2007
DOI: 10.1210/jc.2007-0988
|View full text |Cite
|
Sign up to set email alerts
|

Serum Ghrelin as a Marker of Atrophic Body Gastritis in Patients with Parietal Cell Antibodies

Abstract: Our study demonstrates that ghrelin secretion is negatively affected by autoimmune gastritis, and its serum level represents the most sensitive and specific noninvasive marker for selecting patients at high risk for ABG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 34 publications
1
21
1
Order By: Relevance
“…Ghrelin has been reported to be abnormal in other gastrointestinal diseases such as inflammatory bowel diseases (29), coeliac disease (30)(31)(32)(33) and atrophic gastritis (34)(35)(36). Thus, ghrelin seems to be involved in the pathophysiology of gastrointestinal diseases/disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin has been reported to be abnormal in other gastrointestinal diseases such as inflammatory bowel diseases (29), coeliac disease (30)(31)(32)(33) and atrophic gastritis (34)(35)(36). Thus, ghrelin seems to be involved in the pathophysiology of gastrointestinal diseases/disorders.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature it can be concluded that ghrelin levels in the gastric mucosa significantly decrease with more advanced histopathological changes, especially after the atrophic gastritis stage [34,35] . It has been suggested that the level of this hormone can be considered as one of the markers of gastric mucosal change progression and, at the same time, can be one of the indications for gastroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas ghrelin serum levels were reported to be low, and to be the most sensitive and specific non-invasive marker for gastric body gastritis (30), ghrelin concentration decreased in patients with autoimmune atrophic gastritis and diabetes type 1 (31). In patients with chronic atrophic gastritis acetylated ghrelin levels increased in the gastric body and fundus.…”
Section: Inflammatory and Infectious Gastrointestinal Diseasesmentioning
confidence: 97%